Final Evaluation Report - “Improving oversight in Mozambique's governance” (2016-2019) - FCG International Ltd (FCG International Ltd, 2019)
An external evaluation of the project was conducted in April - May 2019. It looked into the strategy, performance and attainment of the general development goals. The results of the evaluation will be taken into account in the planning of a possible second phase of the project. According to the evaluation, the project is highly relevant both for the strategic partnership between Finland and Mozambique, as well as for the sustainability and inclusiveness of the economic growth arising from the extractive industries and the development of democratic governance. Finnish discretionary government transfers are used to support the Improving Oversight in Mozambique’s Governance 2016–2019 project, which aims to strengthen parliamentary oversight of the management of natural resources in Mozambique. It is a joint project of three organisations; Netherlands Institute for Multiparty Democracy (NIMD), Political Parties of Finland for Democracy (Demo Finland) and Instituto para Democracia Multipartidária from Mozambique (IMD). The project was launched in Mozambique in 2017 and it will be closed at the end of 2019; with a budget of EUR 1,500,000. The evaluation emphasises that strengthening parliamentary oversight is a long-term objective. The project has managed to reach preliminary results in a short time frame in that, for example, Members of Parliament have a better understanding of the challenges met by the extractive industries, and for the first time in Mozambique, there is regular exchange of information and cooperation between national and provincial parliaments. However, performance is not on a sustainable foundation. Sustainable impacts require that a greater number of MPs are trained and the training and research centre of Parliament and the technical secretariats of the provincial parliaments are strengthened. In addition to capacity building, the Parliament should be strengthened by creating wider partnerships and networks with other actors in society. In order to consolidate the results of the project and to improve their sustainability, the evaluation strongly recommends the Ministry for Foreign Affairs to continue the project in cooperation with the new Parliament, which will be elected in October 2019, and with provincial parliaments. It would be useful for the new MPs starting their work at the beginning of 2020 that they make use of the materials produced during the project and consult the MPs who were trained during the project. Additionally, the evaluation recommends the Ministry for Foreign Affairs to continue the project with the same partners, because they have managed to establish well-functioning and confidential relations with the Parliament and other political actors.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; decentralization / descentralização; governance / governação

Implement - Outcome Harvesting|Civicus - CIVICUS (CIVICUS, 2019)
Outcome Harvesting is a M&E methodology used to identify, describe, verify and analyses the changes brought about by a campaign, support or advocacy initiative (see Better Evaluation or Winter School 2019 presentation by Outcome Mapping Learning Community). In Outcome Harvesting, one collects evidence of change (‘outcomes’ – e.g. changed policy, amended or stopped legislation processes, a new coalition formed, shifted voting behaviour) and then works backwards to assess contribution to that change. Please note that the change can also be a negative change, and/or the change cannot be linked to one’s own contributions but rather to those of other actors. It may be referred to as Outcome Mapping methodology. However, in Outcome Harvesting, there are also other methodologies used during the harvest process. Outcome harvesting can be used for ongoing monitoring throughout a project or programme, in order to produce real-time information on change. It can also be used with evaluation or impact assessments during projects or programmes, at the end of a project, or some time after they have been completed. Outcome Harvesting involves participation with different stakeholders. According to Wilson-Grau (2015) participation is described by the methodology’s main developer as necessary for a successful outcome harvesting process and product. Moreover, it is considered most useful under three conditions (see Ricardo Wilson-Grau and Heather Britt 2012): Focus on outcomes rather than activities: It is not designed to assess whether activities were carried out according to plan, rather than assessing what has changed and why. Complex programming contexts: Outcome Harvesting is suitable for complex programming context where the relationship between the cause and the effects is not fully understood. Examples of complex situations could include in areas such as advocacy, mobilization, capacity development, empowerment or network development. Monitoring and evaluation: Outcome Harvesting can also be used when the purpose as an M&E exercise is to learn about the change and understanding why those changes occurred.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia